2018
DOI: 10.1002/cpt.1233
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Prescription of Strong CYP1A2 Inhibitors and the Risk of Tizanidine‐Associated Hypotension: A Retrospective Cohort Study

Abstract: Tizanidine, a widely used muscle relaxant that can lower blood pressure, is metabolized by the cytochrome P450 1A2 (CYP1A2). We studied 1,626 patients prescribed tizanidine and 5,012 prescribed cyclobenzaprine concurrently with a strong CYP1A2 inhibitor. The primary outcome was severe hypotension, defined as systolic blood pressure (SBP) ≤ 70 mmHg during periods of drug co-exposure. Severe hypotension occurred more often in the tizanidine group (2.03%; n = 33) than the cyclobenzaprine group (1.28%; n = 64); od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Ciprofloxacin at doses of 500 mg twice daily increased the peak concentration and AUC (0-∞) of tizanidine by 7-fold and 10-fold, respectively, resulting in hypotension, somnolence, dizziness, and reduced psychomotor performance [6]. Other effects resulting from the coadministration are significant decrease of heart rate, blood pressure, and body temperature [5,9]. In the current study, the most frequently reported terms were related to the central nervous and the cardiovascular system, such as hypotension, somnolence, fatigue, and asthenia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ciprofloxacin at doses of 500 mg twice daily increased the peak concentration and AUC (0-∞) of tizanidine by 7-fold and 10-fold, respectively, resulting in hypotension, somnolence, dizziness, and reduced psychomotor performance [6]. Other effects resulting from the coadministration are significant decrease of heart rate, blood pressure, and body temperature [5,9]. In the current study, the most frequently reported terms were related to the central nervous and the cardiovascular system, such as hypotension, somnolence, fatigue, and asthenia.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with similar ADR profiles administered together may cause synergistically amplified reactions and higher numbers of concomitant drugs may increase the risk to develop toxicity. Common ADRs of tizanidine include antihypertensive and CNS depressive effects [ 2 , 5 , 9 , 20 ]. In our study, also the nine most frequently coadministered drugs are associated with antihypertensive and CNS depressive effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is extensively metabolized via cytochrome P450 (CYP) 1A2 in the liver before it reaches the systemic circulation [2]. Therefore, coadministration with CYP1A2 inhibitors is not recommended and a formal contraindication exists for patients treated with strong CYP1A2 inhibitors, such as the fluoroquinolone antibiotic ciprofloxacin [5].…”
Section: Introductionmentioning
confidence: 99%